2D nanosheet enabled thin film nanocomposite membranes for freshwater production – a review. Issue 11 (19th May 2021) - Mallya, Deepak Surendhra; Dumée, Ludovic F.; Muthukumaran, Shobha; Lei, Weiwei; Baskaran, Kanagaratnam
Abstract : This review presents state-of-the-art progress in 2D-enabled TFN membranes for RO and NF applications in water treatment with emphasis on impact of 2D nanosheet on membrane properties, performance, and its associated challenges. Abstract : Thin film composite (TFC) membranes are primarily used for commercial desalination and water purification applications by both reverse osmosis (RO) and nanofiltration (NF). The incorporation of 2D nanosheets across TFC membranes during interfacial polymerization generates a novel class of separation materials with higher permeability and selectivity, as well as greater chemical and thermal stabilities, supporting antifouling behaviours. Here, the potential of 2D nanosheet-based TFN to engineer materials of enhanced separation properties are critically discussed, in light of defect engineering approaches, types of unique properties of various nanosheets and Case studies on 2D nanosheet-based TFN membranes are critically compared, and properties-to-performance relationships are established to reveal trends and provide insights on the future of the field. The impact of the 2D nanosheets on the surface properties and interactions with solutes in water are extensively discussed. Challenges related to the TFN fabrication processes and leaching of nanosheets over time, which diminishes the scalability and long-term separation performance are also discussed. A vision for advanced and scalable manufacturing synthesis of nanosheets assemblies across or within TFN membranes is also evaluated alongside potential strategies to support the next generation of 2D-enabled separation membranes.